Comparing protocols of DNA extraction from Escherichia coli: Analysis of purity and concentration by gel electrophoresis - Oslaene Alves de Brito; Francisca Alves dos Santos; Tassia Thais Al Yafawi; Cícero Roberto Nascimento Saraiva; Rakel Olinda Macedo da Silva; Lívia Maria Garcia Leandro; Pedro Everson Alexandre de Aquino; Dárcio Luiz de Sousa Júnior; Maria Karollyna do Nascimento Silva Leandro (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Background and objectives: Given the difficulty in establishing an ideal method that can successfully extract bacterial deoxyribonucleic acid (DNA) in Gram-negative bacteria, the objective of this work was to compare protocols for the extraction of bacterial DNA and to report the more practical, faster, and less costly ones.